Anthraquinone repellent seed treatment on corn reduces feeding by wild pigs. (May 2021) - Snow, Nathan P.; Halseth, Joseph M.; Werner, Scott J.; VerCauteren, Kurt C.
Abstract: Wild pigs ( Sus scrofa ) are a destructive invasive species that cause extensive damage to agriculture throughout many regions of the world. In particular wild pigs damage corn more than any other crop, and most of that damage occurs immediately after planting when wild pigs excavate and consume planted seeds. We evaluated whether anthraquinone (AQ), a repellent, could be useful for protecting seed corn from consumption by wild pigs. Specifically, we conducted cafeteria-style tests at 16 bait sites for 6 nights using concentrations of: untreated, 0.5, 1.5, and 3.0% AQ by weight sprayed on whole-kernel corn in AL and TX, USA. We found that repellency for wild pigs was dependent on the AQ concentration, with the greatest repellencies of 95% (AL) and 59% (TX) observed using ~3% AQ. We also found that repellency decreased as the abundance of wild pigs increased at the bait sites. Raccoons ( Procyon lotor ) did not appear to be repelled by the AQ-coated corn, but white-tailed deer ( Odocoileus virginianus ) and mule deer ( O. hemionus ) were. Overall, our results show promise for the development of a repellent for treating seeds to protect them from wild pigs. We recommend the next steps of testing of the 3% concentration of AQ on corn seeds that are planted underground to optimize the best potential protection against damage from wild pigs. Highlights: A 3% anthraquinone spray treatment on corn showed promise for reducing consumption by wild pigs. Repellencies of 95% and 59% on treated corn were observed in Alabama, and Texas, respectively. Repellency declined as larger groups of wild pigs fed on the treated corn.